Regulation of hepatitis B virus gene expression by its two enhancers. - Su, H (1992)
Hepatitis B virus (HBV) infection causes acute and chronic hepatitis and is closely associated with the development of hepatocellular carcinoma. The principal site of HBV infection is liver, and HBV actively replicates in hepatocytes. Two regions of the HBV genome have been shown previously to display properties of a transcriptional enhancer. In this study, we show that either of the two HBV enhancers can activate all three major HBV promoters in several human hepatoma lines, and the cooperative action of the two enhancers ultimately affects overall activity of the three promoters. In addition, our data suggest that HBV gene expression may be differentially regulated by its enhancers. HBV infection causes chronic liver inflammation and hepatocyte regeneration. It has been proposed that progressive accumulation of mutations during the regenerative hyperplasia may lead to alterations in the differentiation state of hepatocytes. Thus, the development of two differentially regulated enhancers may reflect a strategy of HBV to replicate efficiently in less differentiated hepatocytes during hepatocyte regeneration or hepatocarcinogenesis.